(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Electro-responsive nanocomposite hydrogels based on gelatin, partially neutralized acrylic acid (PAAc), and acid-functionalized multiwalled carbon nanotubes (MWCNT-COOH) were developed and evaluated as potential smart drug delivery systems. The successful functionalization of pristine MWCNTs was confirmed by the shift in characteristic X-ray diffraction (XRD) peaks, while the presence of MWCNT-COOH peaks in the nanocomposite hydrogel verified their effective incorporation into the polymer matrix. Scanning electron microscopy (SEM) revealed distinct morphological changes following acid functionalization and demonstrated the uniform dispersion of MWCNT-COOH within the hydrogel network, resulting in a smooth and homogeneous surface. Swelling studies showed that increasing MWCNT-COOH content reduced the swelling percentage in the absence of an electric field, whereas the application of a 10 V electric field significantly enhanced swelling, confirming the electro-responsive nature of the hydrogels. In vitro hemolysis assays indicated excellent blood compatibility, highlighting their suitability for biomedical applications. The electro-responsive release of vitamin B12 was strongly influenced by the ionic strength of the release medium, applied voltage, and MWCNT-COOH concentration. Furthermore, drug release behavior was systematically optimized using response surface methodology based on a central composite design. Overall, the developed Gelatin-g-PAAc/MWCNT-COOH nanocomposite hydrogels exhibit favorable structural, swelling, biocompatible, and electro-responsive characteristics, making them promising candidates for the design of advanced electrically controlled drug delivery systems.